PERAN LEMBAGA PENDIDIKAN DALAM MENGHASILKAN LULUSAN BERKUALITAS DAN BERDAYA SAING TINGGI - Rahmulyana, Anjar; Raman, Raman; Yustiva, Fitriyatul; Junaesih, R.; Halabi, Ahmad; Umalihayati, Umalihayati; Yusuf, Furtasan Ali (Yayasan Education and Social Center, 2024)
This research aims to investigate the role of educational institutions in producing quality and highly competitive graduates. The main focus of this research is to analyze the strategies and policies implemented by educational institutions to improve the quality and competitiveness of their graduates in the job market. This research method involves surveys, interviews, and documentation analysis of several higher education institutions and secondary schools. This research is directed at evaluating the curriculum, teaching methods and supporting facilities provided by educational institutions in creating a learning environment that is conducive to the development of skills and knowledge relevant to the demands of the current job market. Apart from that, this research will also assess the effectiveness of internship programs, collaboration with industry, and career support provided by educational institutions to their students. It is hoped that the results of this research will provide in-depth insight into the efforts of educational institutions to produce graduates who not only have academic competence, but also practical skills and a strong understanding of industry needs. It is hoped that the implications of these findings can become the basis for improving educational policies and practices in order to increase the quality and competitiveness of graduates in this era of globalization.